2014
DOI: 10.3855/jidc.3820
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of TLR2, TLR4, and VDR loci and pulmonary tuberculosis in Moroccan patients

Abstract: Introduction: Toll-like receptors (TLRs) 2, 4, and the vitamin D receptor (VDR) are central components of the innate and adaptive immunity against Mycobacterium tuberculosis (Mtb). TLR2, TLR4, and VDR polymorphisms were previously associated with tuberculosis (TB) and were here investigated as candidates for pulmonary TB (PTB) susceptibility in a Moroccan population group. Methodology: Genomic DNA from 343 PTB patients and 203 healthy controls were analyzed for 12 single nucleotide polymorphisms (SNPs) located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 63 publications
2
19
1
Order By: Relevance
“…We found rs3804099 was not associated with both PTB and LTBI after Bonferroni correction. Our finding was partly similar to the data from a previous study on Mexican patients (24). Indeed, their study suggested that this genotype did not influence the susceptibility to PTB, while the CT genotype was related to TB.…”
Section: Discussionsupporting
confidence: 92%
“…We found rs3804099 was not associated with both PTB and LTBI after Bonferroni correction. Our finding was partly similar to the data from a previous study on Mexican patients (24). Indeed, their study suggested that this genotype did not influence the susceptibility to PTB, while the CT genotype was related to TB.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, associations between the TLR2 genetic diversity and Alzheimer's disease [61] or cognitive function in schizophrenia [62] are highly suggestive of genetically-driven inter-individual ability to modulate neuroinflammatory processes. Of importance is that the TLR2 rs3804099 polymorphism was showed on the one hand to be associated with several inflammatory and infectious diseases including pulmonary tuberculosis, neonatal infection, filariasis, ocular Behcet's disease and cancer [63][64][65][66][67] and to exert a functional impact on the inflammatory response on the other [65,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Such disease is characterized by cholangitis with remarkable recruiting inflammatory cells in the early stage of infection, followed by hyperplasia of the intrahepatic bile ducts, cholangiofibrosis, and cholelithiasis in the host liver during the chronic stage [4]. Moreover, as a group I carcinogen, C. sinensis can induce human cholangiocarcinoma in chronically infected people [5][6][7].…”
Section: Introductionmentioning
confidence: 99%